Evaluasi Sistem Pencahayaan dan Penggunaan Energi Listrik pada Lampu Sorot di Gelanggang Olah Raga Kridosono Yogyakarta - Agityawan Ranga Manyurang; Bambang Sudibya (Institut Teknologi Dirgantara Adisutjipto, 2022)
Kridosono Yogyakarta sports building is one of the sports facilities in the Kotabaru Yogyakarta. As the function of the exercise routine for this sports building is basketball and volleyball, the use at night of course uses an artificial lighting system. Artificial lighting, especially spotlights that have been installed based on information from the sports building manager, is still lacking in the sense of lack of light. For this reason, this study aims to evaluate the lighting system and calculate the use of floodlight electrical energy after and before the evaluation. The results showed that the average lighting level in the Kridosono Sports Building Yogyakarta did not meet the minimum standard of 200 Lux. Recommendations through the calculation of lighting levels obtained results of 211.2 lux and 202.75 lux. For the DIALux 4.13 simulation using a Philips BVP130 1xLED210/740 spotlight and a Philips BVP130 1 xLED172/830 spotlight, the results are 240 lux and 230 lux. The total electrical energy consumption of the floodlights before the evaluation was 752 kWh/month and after being re-planned by replacing the spotlights using Philips BVP130 1xLED172/830 of 678.3 kWh/month so as to save electrical energy by 9.8% and using Philips BVP130 spotlights 1xLED210/740 electricity consumption is 670kWh/month so that it saves electrical energy by 10.9%.